2009
DOI: 10.1002/pc.20948
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characteristics of glass bead‐ and wollastonite‐filled isotactic‐polypropylene composites modified with thermoplastic elastomers

Abstract: Microstructural characteristics of isotactic-polypropylene/glass bead (iPP/GB) and iPP/wollastonite (iPP/W) composites modified with thermoplastic elastomers, poly(styrene-b-ethylene-co-butylene-b-styrene) copolymer (SEBS) and corresponding block copolymer grafted with maleic anhydride (SEBS-g-MA), were investigated. Scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and dynamic mechanical analyses (DMA) showed that the iPP/SEBS and iPP/SEBS-g-MA blends were partially compatible two-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 103 publications
(254 reference statements)
0
17
0
Order By: Relevance
“…Previous studies by the authors [2] showed that the stiffness of neat PP is sufficient for the use in FFF. As the incorporation of glass-spheres in PP increases the Young's modulus [30], the stiffness requirement related to 3Dprinting is met by all filled composites of the present work. However, it was shown that only filled polypropylene compounds with a strength of minimum 13 MPa were successfully printable using a similar printing setup as described in "Impact Specimen Preparation" [2].…”
Section: Tensile Propertiesmentioning
confidence: 73%
See 2 more Smart Citations
“…Previous studies by the authors [2] showed that the stiffness of neat PP is sufficient for the use in FFF. As the incorporation of glass-spheres in PP increases the Young's modulus [30], the stiffness requirement related to 3Dprinting is met by all filled composites of the present work. However, it was shown that only filled polypropylene compounds with a strength of minimum 13 MPa were successfully printable using a similar printing setup as described in "Impact Specimen Preparation" [2].…”
Section: Tensile Propertiesmentioning
confidence: 73%
“…1b compares the tensile test results of the glass spherefilled PP compounds containing am.PO to those of neat PP. As expected, for both materials, the addition of am.PO leads to an increase in E Y due to the dilution of the composite with the rubbery and more ductile material [2,30,87]. Moreover, a reduction in crystallinity due to the addition of an amorphous component may contribute to the E Y enhancement [30] (see "Thermal Properties").…”
Section: Tensile Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to neat PP (T Cryst = 111.4 ± 0.7 °C), all the filled filaments exhibit considerably increased T Cryst , because glass spheres are known to nucleate PP. [12,45,46] The compound containing the smallest filler (PP/E-1) seems to nucleate the PP matrix in the most efficient way. Compared to neat PP, an increase of roughly 12% to 125.3 ± 0.9 °C is observed.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…As expected, the incorporation of spherical fillers as well as the change in the T Ch influences the impact behavior of the printed parts (Figure 9). Independent of the processing conditions, all the composites exhibit a notched impact energy decreased by 70-90% compared to neat PP, because the incorporated microspheres can act as initiation points for defects [20,45,83] and can reduce the impact fracture area. [84,85] A similar decrease in the impact energy by 65% to 80% was observed for 3D-printed Charpy specimens of the same PP compound filled with the broadly distributed glass spheres Spheriglass 3000E in a previous work.…”
Section: Impact Propertiesmentioning
confidence: 99%